The role of diffusion weighted magnetic resonance imaging in oncologic settings - Bozgeyik, Zulkif; Onur, Mehmet Ruhi; Poyraz, Ahmet Kursad (Ame Publishing Company, 2013)
There is growing interest in the applications of diffusion-weighted-imaging (DWI) in oncologic area for last ten years. DWI has important advantages as do not require contrast medium, very quick technique and it provides qualitative and quantitative information that can be helpful for tumor assessment. In this article, we present oncologic applications of DWI in the parts of the body. DWI has been applied to the evaluation of central nervous system (CNS) pathologies. Some technologic advances lead to using of DWI in the extracranial sites such as abdomen and pelvis. As well as tumor detection and characterization, DWI has been widely used for predicting and monitoring response to therapy. One of the most prominent contributions of DWI is differentiation of between malignant and benign tumoral process. Apparent-diffusion-coefficient (ADC) value is quantitative parameter of DWI which reflects diffusion movements of water molecules in various tissues. Most of the studies suggested that malignant tumors had lower ADC values than benign ones. DWI may be a routine sequence in oncologic settings and it provides much useful information about tumoral tissue. We think it can be added to conventional magnetic resonance imaging (MRI) sequences.
Keywords: Diffusion-weighted MRI; oncology; magnetic resonance imaging (MRI)